Formation of skills and consumer values domain and indicators among students in institute of higher learning - Dol, Nurazlina; Abu Bakar, Elistina; Md Jusoh, Zuroni; Muhammad Arif, Afida Mastura (International Organization of Scientific Research, 2018)
Consumer’s skills and consumer’s values are among the key components to cultivate consumers to have good consumers’ practices. However, there is a lack of measuring tools to gauge consumer skills and consumer values. The objective of this study is to identify the domains and indicators of the consumer’s skills and values among students in institute of higher learning. This study utilizes qualitative data methodology which adopts Nominal Group Technique (NGT) as a data collection technique. It comprises of two series of NGT among academicians, regulators, policymakers, members of consumer associations and higher education students. The results of the NGT show that there are ten identified consumer skills, namely the ability to speak, find information, compare prices, make choice, identify products, advocacy, differentiate needs and wants, finance, security, and the environment. As for the consumer’s values, eleven values were derived, namely justice, humanity, security, environment, stability, moderation, knowledge, wisdom, money, honesty, and unity. These domains can be used as a foundation to develop consumer’s skills and consumer’s value index in Malaysia. The findings of this study also give important implication to researchers in the field of consumerism, especially instrument development and can be the basis for consumer education in general.